[Antal Kiss 5]
travelling in the GDR, visiting a concentration camp, model of Weimar, lake with swans, agricultural works, glass-house plants, flowers, fruit trees, traveling on bus, fruit selection, mechanized packing, tablet on a building: Franz Liszt Hochschule, Goethe museum, (3 minutes foreign material about a town by night)